VD_FINDINFO HC / 2010 / 67 vom 3. Dezember 2009 - VD Tribunal cantonal (2009)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE, FAUTE | 42 al. 1 CP, 42 al. 2 CP, 43 ch. 1 CP, 47 CP, 411 let. i CPP, 415 CPP